Psycosocial predictors of suicidal ideation in adolescence - Tancred, Hester Maria (University of the Free State, 2010)
South African adolescents - like their peers around the world – struggle to keep their emotional health intact. These problems are revealed by the youths’ involvement in risky activities such as suicidal behaviour. The steady increase in suicidal behaviour in South Africa makes it imperative to understand the contextual resources and dispositional factors which can act as potential protectors in adolescent suicide; and also to understand the psychosocial risk factors experienced by South African adolescents at risk of suicide. Suicidal ideation has been proved to be a good predictor of suicide risk and was therefore taken as the criterion variable in the current study. A high level of suicide risk among the participants was determined by cut off scores of above 31; and low levels by cut off scores of below 16 on the Suicidal Ideation Questionnaire. The adolescents in the present study with a high suicide risk (N=214) brings the incidence of suicidal ideation to 36% for the current study. The primary aim of the present study was to examine the relationship between a contextual resource (social support from family and friends) and suicidal ideation in a community sample of (N=594) grade 8 to 10 learners from an urban area in the Western Cape region, South Africa. Social support from family and friends was measured with The Perceived Social Support from Family and Friends Scale. A hierarchical regression analysis revealed that the support from family and friends explained 21,5% of the variance of suicidal ideation with support from family being more important than support from friends. The unique contribution of the present study was that social support differed for population groups but not for gender and family structure. Secondly, the present study aimed to determine how adolescents with high risk and those with low risk for suicide differed with regard to the dispositional factors of selfesteem, hope, sense of coherence and cognitive style. The 214 adolescents with a high suicide risk and 267 adolescents with a low suicide risk were compared in terms of these dispositional factors. The results from the MANOVA and ANOVA analyses indicated that adolescents with a high risk of suicide displayed lower self-esteem, a weaker sense of coherence and made more negative attributions for negative life events. The third aim of the present study was to explore the psychosocial risk factors experienced by adolescents. The participants with a high risk of suicide (N=214) were asked to give their opinions on adolescent suicide. These qualitative responses were analysed using the method of content analysis. From this analysis it was clear that adolescents experienced numerous risks, which were given in the following order of prominence: individual factors (substance abuse; negative emotional experiences; self-esteem; problem-solving ability and hope for the future); family environments and family relationships; peer group and romantic relationships; stressful life events; and socio-economic factors. The findings from the present study suggested that a supportive family; a healthy selfesteem; a sense of coherence; and an optimistic explanatory style could be protective mechanisms in lowering the identified risks of substance abuse, feeling stressed, a troubled family environment and poor parent-child relationships found among suicidal adolescents in South Africa.
Keywords: Thesis (Ph.D. (Psychology))--University of the Free State, 2010; Teenagers -- Suicidal behavior -- South Africa; Interpersonal relations in adolescence; Suicide -- Risk factors -- South Africa; Youth -- Suicidal behavior -- South Africa; Suicide -- South Africa -- Psychological aspects; Cognitive style; Sense of coherence; Self-esteem; Hope; Protective factors; Psychosocial factors; Social support; Suicide ideation; Adolescence